The impact of digital health interventions in the treatment and management of perinatal depression: a systematic review - Mahlalela, Nongcebo Nokukhanya (Department of Human Biology, 2026)
Background Perinatal depression, a significant complication of pregnancy and the postpartum period is common amongst women within the reproductive age. Despite its significant contribution to the disease burden and being one of the leading factors of disability, mental healthcare for treating and managing perinatal depression remains a low priority globally (Almond, 2009; Dadi et al., 2020; Rahman et al., 2013). Digital health interventions (DHIs) are implemented to address the accessibility and cost barriers related to mental healthcare. This systematic review aims to examine the impact of the integration of DHIs and psychological approaches in decreasing the symptoms of perinatal depression amongst women aged between 16 and 55. An assessment of the effectiveness, acceptability, usability and cost-effectiveness of the mentioned DHIs will be conducted. Methodology The systematic search was conducted in six academic health databases: PubMed, Cochrane, CINHAL, PsycInfo, PsycArticles and Medline. The year of publication of the studies was between the first of January 2007 and the thirtyfirst of December 2020. Randomised control trials (RCT), quasi-experimental, and cohort studies assessing the effectiveness of DHIs in treating perinatal depression were included. The study participants were limited to pregnant and postpartum women aged 16 to 55. The psychological interventions include cognitive behavioural therapy (CBT), interpersonal psychotherapy (IPT), psychoeducation, peer support and counselling. Furthermore, the DHIs included mobile health applications and telephone-based and web-based solutions. The studies that met the inclusion criteria after screening were included for data extraction. Lastly, a narrative analysis was conducted to synthesise the results from the included studies. Results Out of 271 articles, 24 met the inclusion criteria, where randomised control trials (RCT) were the most predominant studies for eligibility (n = 21). The participants consisted of perinatal (n = 1), postpartum (n =18) and pregnant women (n =5). Surprisingly, only one study was conducted in a low-and-middle-income country (LMIC). Fifteen studies utilised web-based interventions: five used telephonebased solutions, while only four used mobile health applications. For the review outcomes, twenty studies assessed the effectiveness, while 13 assessed the acceptability. Notably, the outcomes of cost-effectiveness (n =2) and usability (n = 3) were assessed in only a few studies. Discussion The findings of the present review indicate the success of DHIs in treating perinatal depression, especially when integrated with the predominant psychological approaches such as CBT. However, the shortage of literature that evaluates its efficacy in LMICs highlights a significant research gap. Furthermore, due to its limited availability in literature, the outcomes of cost-effectiveness and usability need to be further assessed in future research. The systematic review protocol has been successfully registered with the International Prospective Register of Systematic Reviews (PROSPERO), registration number: CRD42021264253. Conclusion The integration of CBT, peer support and psychoeducation with digital health reports positive outcomes among the perinatal population. Despite the positive outcomes reported in the application of CBT, psychoeducation and peer support, disproportionate access to digital devices among the LMICs remains, calling for an increase in the implementation of telehealth instead of web-based interventions. Keywords Digital health, mHealth, eHealth, telemedicine, perinatal depression, low-andmiddle-income countries, mental health, maternal health.